2018
DOI: 10.1182/blood-2017-04-773838
|View full text |Cite
|
Sign up to set email alerts
|

Reclassifying patients with early-stage Hodgkin lymphoma based on functional radiographic markers at presentation

Abstract: The presence of bulky disease in Hodgkin lymphoma (HL), traditionally defined with a 1-dimensional measurement, can change a patient's risk grouping and thus the treatment approach. We hypothesized that 3-dimensional measurements of disease burden obtained from baseline F-fluorodeoxyglucose positron emission tomography-computed tomography (PET-CT) scans, such as metabolic tumor volume (MTV) and total lesion glycolysis (TLG), would more accurately risk-stratify patients. To test this hypothesis, we reviewed pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
0
6

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 18 publications
2
74
0
6
Order By: Relevance
“…Although TLG in one study was predictive of PFS , MTV performs better in multivariate analyses indicating that degree of FDG avidity per se is less important in HL. MTV remained prognostic after adjustment for clinical risk factors . The role of quantitative FDG‐PET/CT for outcome prediction in DLBCL is less clear with some investigators reporting that MTV (both VOI 2.5 and VOI 41 ) is prognostic of outcome and others not finding an association .…”
Section: Quantitative Pet/ctmentioning
confidence: 93%
See 2 more Smart Citations
“…Although TLG in one study was predictive of PFS , MTV performs better in multivariate analyses indicating that degree of FDG avidity per se is less important in HL. MTV remained prognostic after adjustment for clinical risk factors . The role of quantitative FDG‐PET/CT for outcome prediction in DLBCL is less clear with some investigators reporting that MTV (both VOI 2.5 and VOI 41 ) is prognostic of outcome and others not finding an association .…”
Section: Quantitative Pet/ctmentioning
confidence: 93%
“…Nevertheless, a growing body of literature shows that quantitative FDG‐PET/CT can be used to risk stratify patients with lymphoma. In primary and relapsed HL, baseline MTV predicts progression free survival (PFS) both when applying the VOI 2.5 and the VOI 41 methods. Although TLG in one study was predictive of PFS , MTV performs better in multivariate analyses indicating that degree of FDG avidity per se is less important in HL.…”
Section: Quantitative Pet/ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine zunehmende Anzahl von Studien berichtet von der prognostischen Aussagekraft prätherapeutischer oder (seltener) Interim-Response (semi)quantitativer [18F]FDG-PET-Parameter, welche neben SUV-Werten auch metabolisches Tumorvolumen (MTV) und totale Glykolyse im Lymphomgewebe (TLG, Produkt aus MTV und mittlerem SUV) umfassen. Die bisherigen Ergebnisse lassen auf eine Anwendbarkeit über ein breites Spektrum verschiedener Lymphomsubtypen schließen, welches u. a. Hodgkin-Lymphome, DLBCL, follikuläre Lymphome, MALT-Lymphome und T-Zell-Lymphome umfasst [32][33][34][35][36][37]. Diese prognostische Aussagekraft, welche in den meisten Fällen auf die Vorhersage des progressionsfreien Überlebens (PFS, "progression-free survival") oder Gesamtüberlebens (OS, "overall survival") abzielt, ließ sich für Patienten unter verschiedenen Therapien nachweisen.…”
Section: Quantitative Parameter Und Prognostikunclassified
“…Notably, many previous studies have also shown that pretherapeutic SUVs, metabolic tumor volumes (MTV), and total lesion glycolysis (TLG) extracted from [ 18 F]FDG‐PET enable outcome prognostication in a variety of histological subtypes, including HL, DLBCL, FL, and also T‐cell lymphomas . In addition, [ 18 F]FDG‐PET has also been evaluated as a tool for risk stratification in clinical trials, and several studies to investigate this topic are still ongoing.…”
Section: Lymphomamentioning
confidence: 99%